2010
DOI: 10.17221/2487-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary selenium sources and levels on performance, selenium content in muscle and glutathione peroxidase activity in broiler chickens

Abstract: The study examined the effect of dietary supplements of sodium selenite (SS), selenium-enriched yeast (Sel-Plex®, SP) and selenium-enriched alga Chlorella (SCH) on growth traits, carcass analysis, selenium content in breast meat, glutathione peroxidase (GSH-Px) activity in breast and thigh meat and liver of chickens. The experiment was realized with seven hundred thirty-five cockerels Ross 308 randomly divided into 7 dietary treatments with 3 replications in each treatment. Chickens were fed a diet sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 25 publications
5
28
1
Order By: Relevance
“…Numerous other studies confirmed the lack of Se supplementation effect the final body weight, slaughter yield and performance in chicken broilers (Wang and Xu, 2008;Ibrahim et al, 2011). Contrary to our findings, no effect of Se was observed on carcass composition or dressing% (Heindl et al, 2010 Kinal et al (2012) reported higher live weight and improved carcass traits in Se-treated groups. However, on the other hand, Sevcikova et al (2006) found no differences in carcass characteristic regarding the weight of breast and thigh muscle, liver, giblets, and carcass yield.…”
Section: Resultscontrasting
confidence: 99%
“…Numerous other studies confirmed the lack of Se supplementation effect the final body weight, slaughter yield and performance in chicken broilers (Wang and Xu, 2008;Ibrahim et al, 2011). Contrary to our findings, no effect of Se was observed on carcass composition or dressing% (Heindl et al, 2010 Kinal et al (2012) reported higher live weight and improved carcass traits in Se-treated groups. However, on the other hand, Sevcikova et al (2006) found no differences in carcass characteristic regarding the weight of breast and thigh muscle, liver, giblets, and carcass yield.…”
Section: Resultscontrasting
confidence: 99%
“…Positive effects of Se on quality and stability of broiler chicken meat have been confirmed by a number of authors (Heindl et al 2010;Wang et al 2011b, c;Yang et al 2012 a.o.). Further studies focus on the effects of Se on egg quality (Attia et al 2010;Skrivan et al 2013).…”
Section: Selenium and Meat And Egg Qualitymentioning
confidence: 79%
“…Effects of various sources and levels of Se in the diet on poultry yield have been subject of a number of studies Attia et al 2010;Heindl et al 2010;Yang et al 2012;Chen et al 2013;Habibian et al 2013;Rama Rao et al 2013 a.o.). The achieved results are not uniform, both negative and positive responses being reported.…”
Section: Selenium and Poultry Yieldmentioning
confidence: 99%
See 2 more Smart Citations